Penerapan Pembelajaran melalui Pendekatan Konstektual (CTL) Untuk Meningkatkan Hasil Belajar Muatan IPA Siswa Kelas VI SDN 46 Mataram - Ardana, I Nyoman Jony (Lembaga Yasin AlSys, 2022)
This study aims to determine whether the contextual approach has an effect on improving student learning outcomes. Science learning with a contextual approach is a learning approach that uses real-world problems as a context for students to learn about critical thinking, as well as to acquire essential knowledge and concepts from the subject matter. The subjects of this study were the sixth grade students of SD Negeri 46 Mataram with the number of students participating in the learning activities as many as 38 students. While the object of research is learning with a contextual approach to the subject of electrical energy, data collection is obtained through initial ability tests, observations, learning outcomes tests, value documentation, and assignments. Learning outcomes tests are carried out at the end of each cycle. This research consisted of two cycles, each cycle consisted of 3 meetings. The results of data analysis showed an increase in the average value of student learning outcomes each cycle. In the first cycle, the average score was 64.75 to 74.67 in the second cycle. An increase also occurred in the average final score of learning outcomes from 64.20 to 75.28. The results showed that the application of learning through a contextual approach could improve science learning outcomes on the subject of electrical energy in grade VI students of SDN 46 Mataram.